A TRANSITIVITY ANALYSIS ON THE THIRD SEMESTER ENGLISH EDUCATION DEPARTMENT STUDENTS’ DESCRIPTIVE WRITING - Nurwanti Nurwanti (PENERBIT LAFADZ JAYA, 2022)
This research analyzes the transitivity process by analyzing the third semester English Education Department students’ descriptive writing at Lakidende Unaaha University. The objectives of the research are to find out the students’ using of the transitivity process and to find out the most dominant of transitivity process in the descriptive writing. The subject of the research was nine students. The research applied descriptive qualitative method. The data was analyzed by Halliday’s theory. In the research, it was found 153 clauses in the six transitivity processes. Material process got 25 times or 16.34 %, mental process obtained 25 times or 16.34 %, relational process was 91 times or 59.48%, behavioral process occurred 8 times or 5.22%, verbal process obtained 1 time or 0.65%, and existential process was 3 times or 1.97%. from the result of analyzing of the transitivity process of the third semester English Education Department students’ descriptive writing at Lakidende Unaaha University, it can be conclude that, students uses six transitivity processes in writing descriptive text. The most dominat is relational process and the lowest is verbal process.